PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH MELALUI SIKAP NASABAH (Studi Pada Bank Muamalat KC. Malang) - Ach Rofiki; Nurhayati Nurhayati (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2020)
This study aims to analyze the effect of corporate social responsibility and service quality on customer loyalty with customer attitude as an intervening variable. The data source of this research is primary data from a sample of customers of Bank Muamalat KC. Poor. Data collection was carried out using purposive sampling by distributing to 100 respondents of Bank Muamalat KC customers. Malang that receives CSR assistance or who knows the implementation of CSR programs. Data analysis tool uses SmartPLS. The results of this study indicate that there is a direct influence of CSR on Customer Loyalty and Customer Quality on customer attitudes, and the indirect effect between service quality on customer loyalty through customer attitudes. While CSR has no effect on Customer Attitude and also Service Quality on Customer Loyalty, while Customer Quality has no indirect effect on customer loyalty through customer attitudes.